Women's Retirement Incomes in New Zealand: A Household Bargaining Approach - John Gibson; Trinh Le; Grant Scobie (New Zealand Government, The Treasury, 2004)
Bargaining models of household wealth accumulation point to a potential conflict of interest between husbands and wives. Since wives are typically younger than their husbands and have longer life expectancy, they have to finance a longer expected retirement period. Thus, it is argued that when women have greater relative bargaining power, households will accumulate higher levels of wealth. However, in this paper, exactly the opposite pattern is reported for New Zealand. To explain this contradiction of the pattern reported in the literature, we construct a consumption smoothing model of saving for retirement. The results suggest that in this setting it may be rational for women with greater bargaining power to favour greater current consumption rather than wealth accumulation. These results indicate the importance of defining the policy context precisely when considering the implications of household bargaining models.
Keywords: D31; J16; J26; 330; Bargaining; Intra-household; Pensions; Retirement; Wealth; New Zealand; Superannuation